Pre-release environmental acclimation enhances wild adaptability of endangered Kaluga sturgeon (Huso dauricus): insights from digestive, immune, and gut-microbiome perspectives - Zhai, Cunhua; Sun, Wentao; Li, Yutao; Han, Haoxiang; Zhang, Ying; Ma, Bo (Frontiers in Microbiology, 2025)
IntroductionPre-release environmental acclimation is an effective strategy for improving post-stocking survival and restoring wild genetic resources in hatchery-reared juveniles. However, environmental acclimation protocols for the endangered Kaluga sturgeon (Huso dauricus) are currently non-existent.MethodsHere, cultured H. dauricus were transferred to a tributary of the Songhua River in autumn and exposed to an in-situ environmental acclimation protocol for 30 days. Subsequently, a hatchery control (HK) and seven environmental acclimation groups—HC1 (day 2), HC2 (day 5), HC3 (day 10), HC4 (day 15), HC5 (day 20), HC6 (day 25) and HC7 (day 30)—were monitored for feeding rate, digestive and immune enzyme activities, immune-gene expression, and gut microbiota change.ResultsDuring the initial phase of wild conditioning, feeding rate remained negligible until HC2 group, then increased to 66%, 88.89% and 100% in groups HC4, HC5 and HC6, respectively. Meanwhile, digestive enzyme activities stabilized between groups HC4 and HC5, and immune enzyme activities in the wild-conditioned sturgeon were markedly higher than those of the control group. In addition, compared with the control group, the pro-inflammatory cytokine Interleukin-6 (IL-6) was significantly up-regulated, whereas the anti-inflammatory genes Interleukin-10 (IL-10) and Transforming growth factor-beta (TGF-β) were significantly down-regulated in HC4 group (P < 0.05). At the phylum level, the dominant microbiota shifted from Pseudomonadota to Bacillota by day 20 (HC5 group) and thereafter remained stable.DiscussionThis study provides a theoretical framework for characterizing the physiological and biochemical responses of H. dauricus during environmental acclimation and provides a scientific basis for conserving its wild genetic resources.